Wettability and interception in relationship with the seasonal changes on the Fagus sylvatica leaf surface - Klamerus-Iwan, Anna; Kraj, Wojciech (Leśne Prace Badawcze, 2017)
Interception is the amount of water held on the canopy at the end of a rainfall event. Rainfall interception and contact angle of raindrops on the surface of plants has a significant meaning in ecohydrology. Leaves are the plant organs in which during development, changes in the composition of the epicuticular wax can be observed. These differences can be explained by phenological changes. In the present study, there was a hypothesis that seasonal phenological changes of leaf surface can highly affect the amount of rainwater retained by plants (interception) and the angle of contact between the droplets and leaf’s surface. This above-mentioned hypothesis was assessed based on the designed measurement series, combining: 1) direct leaves spraying in various stages of growth with water at a constant temperature 2) images obtained by scanning electron microscope (SEM) to analyse changes in the structure of the epicuticular wax 3) photographic methods, images acquired in the light box 4) measurement and analysis of the angle of contact by using simulated raindrops. The leaves of Fagus sylvatica L. were analysed. Samples were taken in the Niepołomice Forest District (southern Poland) from well-developed crown trees. The result of the experiments conducted makes a database of changes in wettability of raindrops on beech leaves throughout the whole vegetative season. The internal slope of drops ranged from 110°–150° in April up to 20°–40° at the beginning of November. Based on the obtained results, we can classify the degrees of leaf wettability and interception under the influence of morphological changes occurring during the vegetative season.